Bidang Garapan Administrasi dan Manajemen Sekolah Atau Madrasah - Mardiyah Mardiyah; Habib Muhammad Bahaus Suruur; Mujia Yahdillah (Al-Idaroh: Jurnal Studi Manajemen Pendidikan Islam, 2024)
In order to raise the standard of education, human resource management is always linked to management and administration of education. Management can take the shape of agreements and guidelines, or it can take the form of a procedure for maintaining records. It is impossible to isolate educational management and administration from its various facets. We talk about the extent of education management and management procedures in this context. The purpose of management is to streamline organizational work systems and ensure successful and efficient implementation. This essay attempts to clarify how management is being implemented in the education sector, with a focus on the components and domains of school administration work. The "literature review" methodology is employed in this article for data collection and review. The eight components of the school management study include organization, administration, communication, administration/management, human resources/permanent, finance/finance, facilities, and public relations, according to the search results and literature review. Throughout the implementation phase, these eight components are connected. Eight Components Additionally, this is the responsibility of educational administration at the school level, which entails the following three key components of education management: The foundation of education governance consists of students, teachers, and curriculum, with support from five additional elements: organization, money, facilities and infrastructure, governance, business, and public relations.